Remy & Arletta [videorecording (DVD)] - Wittman, Micaela; Scott, Riley Quinn; Benedict, Amy (Synergetic Distribution, 2024)
Remy is under the thumb of her staunchly religious, yet alcoholic and abusive mother. She latches onto her best friend, Arletta, as a coping mechanism, but soon learns that their friendship is more than she realized.